Balanced Scorecard And Organization Performance A Study Of Malaysian Healthcare Industry - Hasnida, Abdul Wahab (UTeM, 2010)
This study attempts to discuss BSC as an approach to performance measurement in Malaysian healthcare. Finally this paper is to provide an overview of the usefulness of the BSC in improving a healthcare management and delivery of healthcare at reduced cost without loss of quality. The needs for healthcare to measure their performance not only to know how the business is performing but also to enable it to perform better. Thus, the ultimate aim of implementing a performance measurement system is to improve the performance of an organization so that it may serve its customers, employees, owners and stakeholders better. Performance measurement literatures have found that the traditional performance measures such as profit, return on investment, sales growth were insufficient in today's rapidly change and intense competitive environment. Thus, the study recommends the use of Balanced Scorecard as the measurement tool in bealthcare organizations. In the study, 1 061 mailed questionnaires were sent to healthcare services in Mel aka, Negeri Sembilan and Johor. Out of this, only 103 responded and data collected were analyzed.Correlation analysis was employed on the data collected. Then it is further analyzed using multiple linear regressions. The findings of this study revealed that BSC usage on healthcare organization has positive effect on their performance. Results are discussed and directions for future research are proposed.